Accountability in Congress - Yap, Marilyn Barua; Yap, Marilyn Barua (Legistrat Academy for Legislation and Strategic Studies,Inc., 2016)
"This book explores the terrain of accountability of legislators to identify and explicate the authoritative sources thereof, the powers, duties and functions of legislators and the actions appurtenant thereto for which they are accountable to the public, the types of legislative accountability, and their corresponding mechanisms of enforcement."--Preface.